Strategi Pengendalian Pencemaran Sungai Bukit Batu di Kabupaten Bengkalis - Zakiah Zakiah; Rahman Karnila; Budijono Budijono (Pelantar Press, 2025)
Bukit Batu River in Bengkalis Regency plays a vital role as a water source for domestic use, irrigation, industry, and transportation. However, increasing domestic and industrial activities have significantly contributed to water pollution. This study aims to analyze the current water quality and socio-economic activities, assess water quality status and pollution load, and formulate pollution control strategies. The research employed field observations, laboratory testing of physical, chemical, and biological water parameters, and SWOT analysis. Results show that parameters such as COD and ammonia exceeded Class II quality standards, indicating a moderately polluted condition. The primary pollution sources include domestic waste, agriculture, and industry. Pollution control strategies were developed based on strengths and opportunities, such as community awareness and active involvement of local government. The study concludes that multi-sector collaboration, environmental education, and improved waste management are essential to reducing pollution loads and preserving the sustainability of the Bukit Batu River's functions.